Convergence of Investment Leads by the Real Rate of Interest: An Empirical Evidence in the Indian Economy - Kumar, Manoj; Sharma, Abhishek; Kumar, Sumit (Asian Journal of Interdisciplinary Research, 2023)
This paper examines the impact of real rate of interest in the determination of investment. The policymaking to pave the way of growth is required to determine the effective rate of interest. Nominal interest rate does not depict the real phenomena of an economy. To capture the real phenomena of Indian economy, quarterly series of GDP deflator, the Nominal Rate of Interest, and Gross Fixed Capital Formation used as a proxy of investment have been used at the base year 2011-12. Real rate of interest is the subtraction of inflation from nominal rate of interest. The investment gap ratio is the difference between actual investment and the time trend value of the investment. The trend value of the investment is obtained by linear time. Standard methods have used to test the robustness of the Aggregate Supply equation by applying Augmented Dickey-Fuller and Phillips-Parron tests to avoid spurious regression. Granger Causality test is also employed to confirm the causal relationship between investment and inflation, and investment and the real rate of interest. The analysis concluded that the real rate of interest plays an important role to induce the investment to achieve desired growth of an economy.